2017
DOI: 10.1080/17461391.2017.1414886
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical insights into the determinants of speed in the fencing lunge

Abstract: For fencing, speed of the lunge is considered critical to success. The aim of this study is to investigate determinants of lunge speed based on biomechanics. Ground reaction force (GRF) and three-dimensional kinematic data were collected from 7 elite fencers and 12 intermediate-level fencers performing maximum-effort lunges. The results showed that elite fencers acquired a higher horizontal peak velocity of the centre of gravity (HPV) and concomitantly a higher horizontal peak GRF exerted by rear leg (PGRF) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 32 publications
7
47
1
Order By: Relevance
“…We found a significant correlation between Vmax ASISm and the ROM of the rear knee extension (r=0.56, p=0.031), as in a previous study (Guan et al 2018) conducted on adult fencers. In agreement with these authors, we think that this correlation is in turn linked to the guard position.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We found a significant correlation between Vmax ASISm and the ROM of the rear knee extension (r=0.56, p=0.031), as in a previous study (Guan et al 2018) conducted on adult fencers. In agreement with these authors, we think that this correlation is in turn linked to the guard position.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the more the knees are flexed in guard position, the wider the extension of the posterior knee will be. Previous studies (Bottoms et al 2013, Guan et al 2018) assert that the lower guard position seems to allow a pre-tensioning which facilitates the higher lunge velocity expression. Moreover, more flexed knees in guard position allow a greater extension of the rear knee during the lunge.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, these activities demand high flexibility of the lower limbs to execute complex movements over large joint amplitude. 17,34 For instance, Preuschl et al 17 reported that specific movements regularly executed in taekwondo involved hip flexed angles (65°, 180° = full hip extension) and knee angles close to full extension (178°, 180° = full extension). Similarly, elite fencers regularly execute lunge with hip flexed (49°) combined with moderated knee extension angles (116°).…”
Section: Discussionmentioning
confidence: 99%